Shelley with Benjamin - Nabugodi, Mathelinda (UCL Press, 2023)
Yet what surprises me most of all at this time is that what I have written consists, as it were, almost entirely of quotations. – Compositions so produced are to poetry what mosaic is to painting. – It is the craziest mosaic technique you can imagine – and the very mind which directs the hands in formation is incapable of accounting to itself for the origin, the gradations, or the media of the process.Shelley with Benjamin: A critical mosaic is an experiment in comparative reading. Born a century apart, Percy Bysshe Shelley and Walter Benjamin are separated by time, language, temperament and genre – one a Romantic poet known for his revolutionary politics and delicate lyricism, the other a melancholy intellectual who pioneered a dialectical method of thinking in constellations. Yet, as the above montage of citations from their works demonstrates, their ideas are mutually illuminating: the mosaic is but one of several images that both use to describe how literature lives on through practices of citation, translation and critical commentary.